Sosialisasi Pembelajaran Berbasis Sumber (Resourch Based Learning) dalam Meningkatkan Penguasaan Materi Matematika di Kelas V MIN 2 Langkat - Enda Lovita Pandiangan; Dian Anggeraini; Nurzakiah Simangunsong; Robi’ul Dzukhry (Universitas Maritim AMNI Semarang, 2022)
This research aims to evaluate the effectiveness of the socialization of resource-based learning in improving mastery of mathematics subject matter in elementary schools. The problem identified is students' low understanding of mathematical concepts caused by less varied learning methods and lack of access to relevant learning resources. The aim of this research is to apply a resource-based approach, which involves the use of various learning materials such as videos, interactive applications, and teaching aids, as well as to evaluate their impact on students' mastery of mathematics material. The research method used includes training for teachers regarding resource-based learning techniques. , implementation of this method in the classroom, and evaluation through observation, interviews, and analysis of student test results. The research results show that the application of resource-based learning significantly improves students' mathematical understanding. Data shows a significant increase in student test scores, active engagement in class, and ability to apply mathematical concepts in real situations. Feedback from teachers also indicated increased confidence in teaching and use of a wider variety of learning resources. Various Lecture Methods, Student Learning Outcomes.